Das schwierige Verhältnis von Kulturkritik und Theorie der Kultur. Plädoyer für eine theoretische Auseinandersetzung mit dem Erbe G. Simmels in der Konzeption von ‘Kultur’ - Adolphi, Rainer (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2016)
The essay argues for taking G. Simmel’s theory of culture (especially Der Begriff und die Tragödie der Kultur, 1911) as a crucial point for guidance regarding conceptional questions and fundamental problems in view of current scientific debates on “culture” – with a theoretical discussion on Simmel’s legacy which hasn’t been sufficiently carried out. Simmel’s work will be shown as a generic explanation of a way of “culture thinking” which also in the current conjuncture of the subject “culture” did not turn obsolete in the course of modern scientific alternatives. Three different scopes are in focus: the term “culture” as a subsequent term of “Geist” (considering the consequences for the relation of empiricism and theory); overcoming harmonistic views of culture (“conflict”); and the capability of the critical thought of “sense” (the objectivity of the cultural “sense”). – At the same time, the “Simmel model” reveals the herein not yet thoroughly resolved (“personalistical”) implications of unity and identity, which are rather concealed and anonymously carried further. In Simmel, they result – again as exemplary – from his tendency of being anthropologically universal in his reasoning and from his strong “philosophy of life” forms of thought.